A case study on creating the public and private spaces within a homestay - Aquino, Pamela Bautista; Florendo, Raquel Baltazar (2010.)
There are no design standards regarding measurements of space specifically made under the Rules and Regulations to Govern the Accreditation of Tourism Related Establishments for a Homestay from the Department of Tourism. (DOT Accreditation Handbook) This disparity in the availability of research data for a homestay (Arduser, L. & Brown, D., 2004) creates limitations in interior space planning designs to situate boundaries for the public and private spaces within the built environment. The research created a proposed renovation model for the selected existing homestays in Saud, Pagudpod, Ilocos Norte. The design was a defined Filipino cultural context of the home, wherein Filipino Hospitality is important to the guests of the homestay. The private and public spaces are categorized by the social interactions and Proxemics within the areas. The study was made to provide a reference for homestay owners and for those families who are planning to convert their residential homes into this type of lodging facility. The research design is a descriptive case study using a qualitative analysis of data. The purposive sampling method was used in selecting the homestays to be studied to enhance the validity of the research. The two samples that have been selected are differentiated as a homestay within a residential home and a homestay detached from a residential home. The intention of this selection was to pinpoint the different circumstances regarding privacy issues that occur. The following instruments were used: document review, participant observation and in-depth Interview. The data gathering procedure was divided into four phases. The first is the acquisition of the homestay accreditation information from the DOT. The second is a site visit to Saud, Pagudpud, Ilocos Norte which was a three-day immersion period in gathering observation data. The next phase was administering an in-depth formal semi-structured interview with the owner of the homestay and the available guests. Lastly, the design programming phase was where the transformation of the analyzed gathered data was made into a proposed model. The homestays in Saud, Pagudpud, Ilocos Norte have undergone construction to extend the houses to accomodate more guests. A significant observation of the study focused on the planning process. Most of the areas in terms of segregation of private and public areas are limited. Homeowners and guests co-mingle with each other. The layout of homestay units do not regulate proper access to different areas which creates an inadequate flow of traffic. A lack of accessibility which is also important in providing privacy was not carefully considered. The homeowners and guests have similar concerns about the improper use of space. The poor arrangement of pieces in the provided space and the insufficient space allotted per area generates the problems of the users. A proposed plan presenting a renovated layout of the selected homestays in Saud, Pagudpud, Ilocos Norte were developed. The space allotment for individuals in the public areas follows the measurements that allow personal distance for interactions based on Proximity standards. Minor changes in existing horizontal divisions were made to show that these changes can be done without having to undergo major construction and considering budget constrains of the homeowners.
Thesis, (BSID)--University of the Philippines Diliman.
Keywords: Space (Architecture)--Psychological aspects